(untitled) (Research, Society and Development, 2025)
Analyze, through an integrative review, the impacts of obesity on the HRQoL of children and adolescents. This is an integrative literature review conducted through searches in the PUBMED, LILACS, and SciELO databases, using descriptors and Boolean operators applied to each source. A total of 11 studies were included. The central theme identified across most studies was health-related quality of life (HRQoL) in the context of child and adolescent health. Significant differences were found in physical HRQoL according to degrees of obesity, with severe obesity showing the lowest scores. Such limitations restrict a full experience of childhood and adolescence, often distancing these individuals from play and sports with peers. Body image emerged as one of the main predictors of a deteriorated perception of quality of life among adolescents. The research highlights the influence of aesthetic pressure and social media comparisons on self-image, exposing psychological distress and socially withdrawn behavior. In light of this scenario, the implementation of comprehensive and early intervention strategies is essential, addressing not only the physical aspects but also the emotional and social dimensions of childhood obesity.